A Specific Targeted-Place Mining Method for a Famous Social Network: Take Wang-Ye Worship in Taiwan for Example - Huang, Yung-Fa; Chen, Jong-Shin; Lin, Chuan-Bi (2018 15th International Symposium on Pervasive Systems, Algorithms and Networks (I-SPAN), 2018)
Facebook is an online social media and social networking service, which is most popular in the world. In recent years, the Location-based Facebook check-in service has become a hot topic. Numerous places and check-in behaviors at these places can form public options for example hot places, high density regions of places. In our life, there are many important activities or things. However, they are very difficult to reveal the influences scientifically such as folk religion. Fortunately, there are many check-ins been did when people visited these places. In this study a specific targeted-place mining method for a famous social network is presented. The belief of Wang-Ye is one of most popular folk religions for Taiwanese. The faith in this god accompanied by ritual rules, folk festivals and other cultural activities, and even become one of leisure activities. Accordingly, Facebook places of Wang-Ye worship in Taiwan are taken for example.